Peran Pesantren dalam Pemberdayaan Janda-Janda (Studi di PP. Al-Hasyimiyah Nurul Jadid) - Hanik Yuni Alfiyah (Proceedings of Annual Conference for Muslim Scholars, 2017)
This article about a pattern to parse the empowerment of widows by Pesantren Al-Hasyimiyah Nurul Jadid and its implications for society. Through a qualitative approach, to put forward some of the following. First, the pattern of the empowerment of widows by Pesantren Al-Hasyimiyah Nurul Jadid is naturalistic (naturally). Widows in auxiliary groups Pesantren Al-Hasyimiyah voluntary (voluntary), in terms of the role of Pesantren Al-Hasyimiyah merely invite the widows to be active in school and community activities. Widows were recruited by way of an offer or ditawarai and / or widows are facing schools to enroll. In schools, the widows of those involved in economic activity, study or religious speech, thereby increasing religious insight. Second, the empowerment of widows by Pesantren Al-Hasyimiyah Nurul Jadid positive implications for community empowerment. When there is a coaching activities addressed to the widows, the event is open to the general public. By doing so, the general public can participate accessing development activities for widows. For example, there are training activities â€œpemulasaran jenazahâ€, which was originally reserved for widows, when the general public to follow the development activities, the schools are happy to allow. Communities around schools who diligently follow development activities by schools become more empowered in terms of independence and stubbornness facing a life. Especially for widows, they are more independent, strong and empowered to live a life without a husband's partner.